2019
DOI: 10.1111/ics.12506
|View full text |Cite
|
Sign up to set email alerts
|

Assessing changes in some facial signs of fatigue in Chinese women, induced by a single working day

Abstract: BACKGROUND: The impacts of physical fatigue upon some facial signs, induced by a whole day work, have been previously described on Caucasian women. This study aimed at assessing those possibly experienced by Chinese working women under comparable conditions. MATERIAL AND METHODS: Standard photographs of 60 Chinese women working in the same company (aged 20-40 years) were taken at three occasions during their working day (just before, at 4 and 8 h). Focusing on facial signs allowed a panel of experts to grade t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…For clinical standardized dataset , SD's range 4–17% and 25–50% for ‘selfies’ images dataset, as a result of differences among lighting conditions. As for the sub‐cohort of 70 Caucasian women graded in live conditions by the quorum of experts this ratio ranges 30–60%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For clinical standardized dataset , SD's range 4–17% and 25–50% for ‘selfies’ images dataset, as a result of differences among lighting conditions. As for the sub‐cohort of 70 Caucasian women graded in live conditions by the quorum of experts this ratio ranges 30–60%.…”
Section: Resultsmentioning
confidence: 99%
“…These skin atlases showed that ageing process differently affects women or men to the same extent and that some changes in facial signs were ethnic specific. Apart from affording a precise description of the changes of facial signs with ageing, in both genders of four ethnics, this approach led to determine that some facial signs are more concerned by the fatigue induced by a single day work, in Caucasian or Chinese women .…”
Section: Introductionmentioning
confidence: 99%
“…As such, it obviously integrates many factors known to influence (at short or long terms) facial skin signs such as fatigue, worries, mood, sun exposure, regular use of cosmetic products etc. [2][3][4][5]20,21 In this work, privilege was given to perceived ages as the latter own social or psychosocial aspects. [22][23][24][25] In addition, whether one (or more) elevated given sign may lead to an "older" judgment by the naïve panel was an underlying issue.…”
Section: Discussionmentioning
confidence: 99%
“…), (v) urban pollution, (vi) solar exposures, (vii) lifestyles, (viii) mood, etc. . However, almost all of these quoted papers focused on women, as major consumers of cosmetic products or aesthetical needs.…”
Section: Introductionmentioning
confidence: 99%